Racial disparities in liver cancer: Evidence for a role of environmental contaminants and the epigenome - Vidal, Adriana C.; Moylan, Cynthia A.; Wilder, Julius; Grant, Delores J.; Murphy, Susan K.; Hoyo, Cathrine (Frontiers in Oncology, 2022)
The incidence of liver cancer has tripled since the early 1980’s, and thus liver cancer has become one of the fastest rising types of cancer and the third leading cause of cancer-related deaths worldwide. In the United States, incidence varies by geography and race, with the highest incidence in the southwestern and southeastern states, and among racial minorities such as Hispanics and Blacks. Prognosis is also poorer in these populations. Established risk factors that are known to contribute to cirrhosis that progresses to liver cancer, cannot fully explain the ethnic disparities observed. Besides genetic predisposition, environmental factors that include chemical and non-chemical stressors are estimated to contribute substantially to ethnic disparities. However, mechanistic insights that can be used for prevention remain limited. We advance the hypothesis that epigenetic mediators can serve as early biomarkers for early detection to decrease disparities. In this review we discuss the current state of the literature, some of these challenges and offer potential ways to surmount them, to reduce liver cancer disparities.